2011
DOI: 10.2337/db11-0589
|View full text |Cite
|
Sign up to set email alerts
|

Prospectively Determined Impact of Type 1 Diabetes on Brain Volume During Development

Abstract: OBJECTIVEThe impact of type 1 diabetes mellitus (T1DM) on the developing central nervous system is not well understood. Cross-sectional, retrospective studies suggest that exposure to glycemic extremes during development is harmful to brain structure in youth with T1DM. However, these studies cannot identify brain regions that change differentially over time depending on the degree of exposure to glycemic extremes.RESEARCH DESIGN AND METHODSWe performed a longitudinal, prospective structural neuroimaging study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
72
3
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 48 publications
3
72
3
2
Order By: Relevance
“…Given the alteration in conscious state that accompanies severe episodes, the focus traditionally has been on hypoglycemia as the explanation for cognitive deficits in children with type 1 diabetes. However, neuroimaging findings are inconsistent, with some studies finding no association between hypoglycemia history and structural brain changes (4,12) while others report positive correlations, but with little consistency between the brain regions affected (5,7,(9)(10)(11). Metaanalytic cognitive studies also provide contrasting findings, with one reporting positive association between hypoglycemia history and cognitive deficit (23) and another finding no association (14).…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Given the alteration in conscious state that accompanies severe episodes, the focus traditionally has been on hypoglycemia as the explanation for cognitive deficits in children with type 1 diabetes. However, neuroimaging findings are inconsistent, with some studies finding no association between hypoglycemia history and structural brain changes (4,12) while others report positive correlations, but with little consistency between the brain regions affected (5,7,(9)(10)(11). Metaanalytic cognitive studies also provide contrasting findings, with one reporting positive association between hypoglycemia history and cognitive deficit (23) and another finding no association (14).…”
mentioning
confidence: 65%
“…There is a growing literature documenting pathophysiological CNS changes (4)(5)(6)(7)(8)(9)(10)(11)(12)(13) and neurocognitive deficits (14)(15)(16)(17)(18)(19)(20)(21)(22)(23) in youth with type 1 diabetes. However, attempts to identify specific diabetes-related risk factors for CNS compromise have produced inconclusive findings.…”
mentioning
confidence: 99%
“…One possible explanation for our finding of later age of onset being associated with lower connectivity is that the onset of T1DM and the associated changes in glycemic control may have coincided with this period. Several studies of children with T1DM have detected differences in regional brain volumes (46)(47)(48) and a study of young T1DM patients (< 10 years) found a negative association between age of onset and radial diffusivity, suggesting that earlier age of onset was associated with less myelin integrity (6). We are unaware of any published studies that have investigated functional connectivity in children with T1DM and such studies will be necessary to more fully understand the functional implications of the structural alterations that are being documented.…”
Section: Discussionmentioning
confidence: 99%
“…Морфологическим субстратом КН может быть диффузное двустороннее поражение белого ве-щества больших полушарий (лейкоареоз), которое связано с микроангиопатией [62]. При нейровизуализации головно-го мозга (особенно в стадии манифестации) встречались случаи выраженной церебральной атрофии, отдельные и множественные очаги пониженной плотности в коре полу-шарий и подкорковых субстанциях в сочетании с расшире-нием ликворопроводящих путей, эти изменения были ме-нее выражены, чем у пациентов с СД 2-го типа (р<0,01) [63, 64]. Установлено, что у пациентов с СД 1-го типа КН более выражены при ранней манифестации заболевания, что под-тверждается в экспериментах [65].…”
unclassified